Efeitos da realidade virtual no equilíbrio postural e ativação cortical de idosos saudáveis - Soares, Monalise Dantas (2016)
Introduction: The Brazilian population currently observed an increase in the aging index, a process that triggers physiological changes that alter the structure and function of the body, including the nervous system. These modifications can interfere with the maintenance of postural control becoming responsible for imbalance, limited mobility and hence the possibility of falls, which reinforces the need to provide evidence-based treatments and to ensure the accession of these individuals. In this sense, virtual reality (VR) has become known for providing physical benefits, be motivating and stimulating. Studies have also suggested that training with RV would have more effect on neuroplasticity and transfer of learning, reflecting positively on postural control. Nevertheless, there are few studies of brain and EEG picture that sought to investigate this relationship. In this sense, considering the wide use of VR in rehabilitation and the limited number of studies investigating the impact of this type of training in the Cerebral Cortex, the study questions whether it would be the RV able to improve the balance and modify the pattern of cortical activation individuals elderly. Objective: To analyze the effects of balance training with RV on balance and cortical activation elderly. Methods: This is a case study which involved 03 elderly, who underwent balance evaluation using the Short Physical Performance Battery (SPPB), functional independence, measured by the Functional Independence Measure (FIM) and cortical activation through the Emotiv Epoc®. These were then subjected to 10 balance training sessions using RV with Nintendo wii®, which lasted about 50 minutes each, with a frequency of twice a week. At the end of the whole intervention, participants were reevaluated with the same initial instruments. Results and discussion: 03 elderly women with average of 67.33 years, schooling around 9 years and good cognitive status in the study. It was found after the intervention improved performance in SPPB, characterizing the performance with moderate to good. With regard to the cortical activation, it was found that before the intervention was increased activation of the right hemisphere mainly the frontal and temporal areas at frequencies of 22, 10 and 40 Hz. After the intervention, in addition to activation of these areas, regions posterior parietal started to be more active and those predominantly activated at baseline had a reduction of activation. This resulted in a cortical activation restrained and distributed in Cerebral Cortex. Conclusion: Balance training with RV positively increased the balance of the participating elderly and modified their cortical activation patterns, which seems to have induced cortical changes favorable to motor learning, through practice-oriented and directed toward specific goals.